Role of milk glycome in prevention, treatment, and recovery of COVID-19 - Kaplan, Merve; Şahutoğlu, Arif Sercan; Sarıtaş, Sümeyye; Duman, Hatice; Arslan, Ayşenur; Pekdemir, Burcu; Karav, Sercan (Frontiers in Nutrition, 2022)
Milk contains all essential macro and micro-nutrients for the development of the newborn. Its high therapeutic and antimicrobial content provides an important function for the prevention, treatment, and recovery of certain diseases throughout life. The bioactive components found in milk are mostly decorated with glycans, which provide proper formation and modulate the biological functions of glycosylated compounds. Glycome of milk consists of free glycans, glycolipids, and N- and O- glycosylated proteins. Recent studies have shown that both free glycans and glycan-containing molecules have antiviral characteristics based on different mechanisms such as signaling, microbiome modulation, natural decoy strategy, and immunomodulatory action. In this review, we discuss the recent clinical studies and potential mechanisms of free and conjugated glycans' role in the prevention, treatment, and recovery of COVID-19.